A Century of Profligacy? The Measurement and Evolution of Food Waste. (December 2020) - Bovay, John; Zhang, Wei
Abstract : Food waste has been recognized as an economic issue for at least a century and is gaining tremendous traction in academia as well as in discourse about public policy. The goal of our study is to examine the evolution of food waste over the last several decades at the United States and global levels. We first review the methodologies that have been used to estimate the magnitude of food waste so that the quality of the data can be evaluated. Though with limitations, existing data generally show that for many regions of the world, including the United States, pre-consumer food loss and waste as a share of total supply has been stable in recent decades. However, the aggregate share wasted masks important changes over time. We provide some evidence that food waste has shifted downstream in recent decades, i.e., from producers and processors to retailers and consumers. Through a reflection on the trends in major socioeconomic factors, we hypothesize that this downstream shift has been driven by increases in household incomes, improvements in technology, and changes in culture and institutions.